Determinants of Stress Among Health Students: Academic Pressure, Internal Conditions, and Learning Support - Amalia Salma Anindya; Faqih Jibran Syah Falaifi; Titi Nur Hasanah; Ririn Cahya Dewanti; Salsabila Khoirun Nisa; Aan Sofyan (Interest : Jurnal Ilmu Kesehatan, 2026)
Background: Health students tend to have a higher prevalence of stress compared to those in other study programs, which may negatively affect academic achievement and potentially lead to burnout. Stress is one of the most common psychological problems among health students, primarily triggered by academic demands and limited learning support. This study aimed to determine stress levels and analyze their association with academic pressure, negative internal conditions, and learning support.   Methods: A descriptive-analytic cross-sectional study was conducted among 367 health science students at one university in Surakarta, Indonesia, selected using accidental sampling. Stress levels were measured using the Depression Anxiety Stress Scale (DASS-21) along with a questionnaire assessing stress-related determinants. Data were analyzed using cross-tabulation and chi-square tests to examine the association between determinant factors and students’ stress levels. Results: Data analysis showed that 51.0% of students experienced mild stress, 43.9% had normal stress levels, and 5.2% experienced severe stress. Academic pressure, negative internal conditions, and limited learning support were significantly associated with stress levels (p < 0.001). Students with high academic pressure and limited learning support were more likely to experience mild to severe stress. Conclusion: Student stress levels are significantly influenced by academic demands, internal psychological factors, and learning support availability. Strengthening academic assistance, psychological support, and learning resources is essential to reduce student stress and improve well-being.